2019
DOI: 10.3889/oamjms.2019.663
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Vitamin D Level and Serum TNF-α Concentration on the Severity of Chronic Obstructive Pulmonary Disease

Abstract: Background: Chronic Obstructive Pulmonary Disease (COPD) is a chronic inflammatory disease and disturbed bacterial clearance. Vitamin D deficiency is sometimes observed in COPD patients and as significant roles in increasing inflammation of airway obstruction and systemic obstruction, increasing proinflammatory cytokine including TNF-α, reduction of bacterial clearance and increase exacerbation risk due to infection. Also, vitamin D plays significant roles in the metabolism of calcium and mineralization of bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…When the body's inflammatory cells are activated, the body releases mass inflammatory mediators, which destroy the normal structure of the lungs, [26,27]. TNF-α is one of the most extensively explored cytokines in COPD, with its serum concentration positively correlated with the degree of airway obstruction and COPD severity [28]. IL-6 is a pleiotropic cytokine that acts as a proinflammatory mediator and an inducer of acute-phase responses, and its serum level has a positive connection with the acute exacerbation of COPD [29].…”
Section: Discussionmentioning
confidence: 99%
“…When the body's inflammatory cells are activated, the body releases mass inflammatory mediators, which destroy the normal structure of the lungs, [26,27]. TNF-α is one of the most extensively explored cytokines in COPD, with its serum concentration positively correlated with the degree of airway obstruction and COPD severity [28]. IL-6 is a pleiotropic cytokine that acts as a proinflammatory mediator and an inducer of acute-phase responses, and its serum level has a positive connection with the acute exacerbation of COPD [29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other studies have shown no significant change between serum vitamin D and FEV 1 or FVC ( 51 , 52 ), which is likely due to comorbidities. Possible mechanisms responsible for improved lung function with vitamin D sufficiency include airway remodeling ( 53 ) and immune dysregulation ( 54 , 55 ). Nevertheless, there are conflicting data on the relationships among vitamin D deficiency, insulin resistance and type 2 diabetes mellitus.…”
Section: Vitamin D Arsenic Type 2 Diabetes Mellitus and Lung Functionsmentioning
confidence: 99%
“…Among the published clinical studies, a hospital-based cross-sectional study reported that increased TNF-α level and low serum vitamin D concentrations are associated with airway obstruction in COPD patients. These results were predictable, knowing that TNF-α plays essential roles in pathogenesis and inflammatory responses in COPD, and that vitamin D has a modulator effect on TNF-α [ 40 ].…”
Section: Vitamin D and Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%